Sailing and sports medicine: a literature review - Allen, J. B.; de Jong, M. R. (British Journal of Sports Medicine, 2006)
Sailing medicine has been mainly addressed by healthcare professionals who happen to sail. Although there has been an increase in the number of studies of various aspects of sailing over the last 15 years, efforts to advance evidence based knowledge of sailing and sports medicine face unique obstacles. Recent interest in research by groups such as Olympic and America`s Cup teams has produced beneficial changes.